Immunohistochemical evaluation of HLA-G and FoxP3+ T regulatory cells in oral cavity and lower lip squamous cell carcinomas - Amanda Katarinny Goes Gonzaga; Hellen Bandeira de Pontes Santos; Janaina Cristiana Oliveira Crispim; Lélia Batista de Souza; Gustavo Martelli Palomino (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract: Human Leukocyte Antigen G (HLA-G) is a molecule involved in the tumor immunosuppression and also in the generation of regulatory T (Treg) cells, thus leading to evasion to the immune system host, and consequently, contributing to tumor progression in several cancers. The aim of this study was to evaluate the immunoexpression of HLA-G by tumor cells and FoxP3+ Treg cells in 25 oral tongue squamous cell carcinomas (SCCs) and 25 lower lip SCCs and analyze their relationship with clinical parameters. HLA-G expression was higher in oral tongue SCCs than in lower lip SCCs. In oral tongue SCCs and lower lip SCCs, no association between HLA-G expression and clinical parameters (tumor size, lymph node status, distant metastasis, and clinical stage) was verified (P>0.05). FoxP3+ Treg cells were detected along the tumor invasive front in all cases of oral tongue and lower lip SCCs. In oral tongue SCC cases, the number of Treg cells tended to be higher in smaller tumors, tumors without regional lymph node metastasis, and tumors in early clinical stages, but the difference was not statistically significant (P>0.05). A significant positive correlation was found between the expression of HLA-G by neoplastic cells and Treg cells in lower lip SCCs (p = 0.008). Our findings suggest the involvement of HLA-G and Treg cells in the modulation of immune responses in oral tongue and lower lip SCCs. This interaction between HLA-G and Treg cells may represent an evasion mechanism in these malignancies.